The Oxford handbook of Japanese cinema - Miyao, Daisuke (Oxford handbooks online Literature, 2014)
This text provides a multifaceted single-volume account of Japanese cinema. It addresses productive debates about what Japanese cinema is, where Japanese cinema is, as well as what and where Japanese cinema studies is, at the so-called period of crisis of national boundary under globalization and the so-called period of crisis of cinema under digitalization.
https://katalog.adlr.link/Record/0-165334623X